A review on malaria eradication: what hope for Nigeria? - E.C. Amadi (Journal of Applied Sciences and Environmental Management, 2016)
Malaria and its transmitting vectors are household names. Malaria which helped Africa from the venomous fangs of colonialism has turned to be the bane of development in tropical countries including Nigeria. The factors which promote prevalence of the disease and its transmission dynamics are well discussed in this review paper. As a corollary to the above, sundry recommendations are made. It is hopeful that Nigerian government and other African countries where malaria and its vectors are endemic would exploit these noble ideas as recommended. Also, if the limited grants by donor agencies are properly utilized coupled with the involvement of the right personnels, it is possible that Nigeria will achieve the eradication of malaria.